Determination of Thermal Properties of Carbon Materials above 2000 °C for Application in High Temperature Crystal Growth - Ihle, Jonas; Wellmann, Peter (Crystal Research and Technology, 2025)
This work reports on the determination of the heat conductivity of high temperature stable carbon materials in the temperature range well above 2000 °C where classic material characterization methods fail. Dense graphite (DG) materials as well as rigid and soft felt isolation (RFI/SFI) components have been investigated which are used during crystal growth of SiC by the physical vapor transport method (PVT) in the temperature regime of 2000 and 2400 °C. The applied materials characterization methods include low temperature physical heat conductivity measurements using laser flash analysis (LFA) in the temperature range 25–1200 °C, data extrapolation to elevated temperatures up to 2400 °C, and a correlation of heating processes and computer simulation of the temperature field of different hot zone designs. Using this approach, the calculated temperatures and experimentally determined values with an error of less than ± 2% at 2400 °C can be merged.
CRIS-Team Scopus Importer:2025-01-31
Keywords: carbon materials; high-temperature isolation; SiC PVT growth; temperature field simulation; thermal conductivity